2000
DOI: 10.1093/ije/29.6.969
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer incidence rates in Slovenia 1971–1993

Abstract: The percentage of nulliparous women in the cohort is the most important reproductive variable associated with the trends in the rates, with breast cancer risk predicted to be higher in cohorts with a larger percentage of nulliparous women. As the cohorts born 1932-1946 have a more favourable reproductive pattern as regards breast cancer risk, compared to the 1907-1922 cohorts, age-specific incidence rates in Slovenia would be predicted to decline in the future in the absence of changes in the other risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The APC model has been widely used to analyze the trend of breast cancer incidence (11,(26)(27)(28)(29)(30)(31)(32). These studies all showed a strong birth cohort effect, suggesting the contribution of lifestyle and other possible environmental factors in the pathogenesis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The APC model has been widely used to analyze the trend of breast cancer incidence (11,(26)(27)(28)(29)(30)(31)(32). These studies all showed a strong birth cohort effect, suggesting the contribution of lifestyle and other possible environmental factors in the pathogenesis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During the more recent decades, increased incidence trends have been observed across populations without mammography screening [6,9,[13][14][15], in populations with mammography screening prior to program commencement [4,[10][11][12], as well as in population groups not exposed to screening compared with screened populations [17,22,25], although exact birth cohorts and the temporal turning-points, if any, have varied among different populations. Identified risk factors exerting birth cohort effects on incidence trends include reproductive factors like prevalence of nulliparity, age of menarche, age of first full-term pregnancy and menopause, and nutritional factors including alcohol consumption [43,44].…”
Section: By Initial Bs Screenmentioning
confidence: 99%
“…Increasing trends of female breast cancer incidence over the past few decades have been reported internationally [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16] and in Australia [17][18][19]. These trends generally have been attributed to increased prevalence of risk factors in more recent birth cohorts [1,5,6,8,9,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the prevalence of HRC risk factors has been poorly investigated in Slovenia, we have enough information to explain, at least in part, the spatial distribution of breast cancer risk (risk is higher in the western part of the country) and the rapid rise in breast and prostate cancer incidence. Several studies of the reproductive factors in Slovenia (55)(56)(57) indicate that nulliparity and late first birth (which are both more prevalent in the west of the country) could be responsible for higher breast cancer risk in that part of the country. Reproductive risk factors in Slovenia are also central to the understanding of the increase in breast cancer incidence.…”
Section: The Influence Of Risk Factors On the Burden Of Hrcs In Sloveniamentioning
confidence: 99%